The Building Blocks of Thought - Laurence, Stephen; Margolis, Eric (Oxford University Press, 2024)
The human mind is capable of entertaining an astounding range of thoughts. These thoughts are composed of concepts or ideas, which are the building blocks of thoughts. This book is about where all of these concepts come from and the psychological structures that ultimately account for their acquisition. We argue that the debate over the origins of concepts, known as the rationalism-empiricism debate, has been widely misunderstood—not just by its critics but also by researchers who have been active participants in the debate. Part I fundamentally rethinks the foundations of the debate. Part II defends a rationalist view of the origins of concepts according to which many concepts across many conceptual domains are either innate or acquired via rationalist learning mechanisms. Our case is built around seven distinct arguments, which together form a large-scale inference to the best explanation argument for our account. Part III then defends this account against the most important empiricist objections and alternatives. Finally, Part IV argues against an extreme but highly influential rationalist view—Jerry Fodor’s infamous view that it is impossible to learn new concepts and his related radical concept nativism, which holds that essentially all lexical concepts are innate. Throughout the book, our discussion blends philosophical and theoretical reflection with consideration of a broad range of empirical work drawn from many different disciplines studying the mind, providing a thorough update to the rationalism-empiricism debate in philosophy and cognitive science and a major new rationalist account of the origins of concepts.